A Legal Study on the Mechanism for Resolving Sharia Economic Disputes in the Religious Court - Rajindra Rajindra; Fatma Fatma (Universitas Muhammadiyah Palu, 2025)
This study examines the legal framework and procedural mechanisms for resolving Sharia economic disputes within the Indonesian Religious Court system. As the growth of Islamic finance continues to increase, the number and complexity of disputes related to Sharia-based contracts, financing schemes, and commercial agreements have also risen. This research aims to analyze the principles, legal foundations, and procedural stages used by Religious Courts in handling such disputes. Using a normative juridical approach supported by statutory, conceptual, and case-based analyses, the study explores how judges interpret Sharia principles alongside national law, the effectiveness of dispute resolution procedures, and the extent to which decisions reflect justice and legal certainty for the parties involved. The findings indicate that although the legal basis for Sharia economic dispute resolution is well-established, several challenges remain, including varying interpretations of Sharia, limited expert involvement, and procedural inefficiencies. Strengthening legal harmonization and improving judicial competence are essential for achieving a more effective and equitable dispute resolution system.